Prospective methodologies in hybrid renewable energy systems for energy prediction using artificial neural networks - Rahman M.M.; Shakeri M.; Tiong S.K.; Khatun F.; Amin N.; Pasupuleti J.; Hasan M.K. (MDPI AG, 2023)
alternative energy; artificial neural network; complexity; demand analysis; machine learning; prediction; rural area; smart grid; time series analysis